Morphometric Analysis of Ponyfish (Leiognathus daura) Landed at the PPI Cituis, Tangerang, Banten - Mursawal, Asri; Ruzanna, Arina; Wahyuni, Sri (South East Asian Marine Sciences Journal, 2025)
Leiognathus daura is a small pelagic fish that plays an important role in coastal ecosystems and has economic value for local communities. This study aimed to analyze the length–weight relationship, condition factors, and morphological characteristics of L. daura as a basis for fisheries biology information. A total of 30 specimens were examined morphometrically and meristically. The length–weight regression produced the equation y = 0.9073x + 0.2776 with a coefficient of determination (R²) of 0.2595. The value of b = 0.9073 (< 3) indicates a negative allometric growth pattern, meaning that length increases faster than body weight. Condition factors showed a Fulton's K value of 3.8036 and a relative condition factor (Wr) of 101.0081, suggesting that the fish population is healthy and supported by a favorable aquatic environment. Morphologically, L. daura has a laterally compressed body, small terminal mouth, large eyes, silvery scales, and a forked caudal fin, all of which support schooling behavior and adaptation to shallow coastal waters. The low R² value implies that body weight is influenced by length and environmental conditions, food availability, reproductive status, and fishing pressure. These findings highlight the importance of understanding the biological aspects of L. daura as a foundation for sustainable fisheries management in coastal ecosystems